Revival of raman coherence of trapped atoms - Afek, Gadi; Mil, Alexander (Physical review, 2017)
We perform Raman spectroscopy of optically trapped noninteracting 87Rb atoms, and observe revivals of the atomic coherence at integer multiples of the trap period. The effect of coherence control methods such as echo and dynamical decoupling is investigated experimentally, analytically, and numerically, along with the effect of the anharmonicity of the trapping potential. The latter is shown to be responsible for incompleteness of the revivals. Coherent Raman control of trapped atoms can be useful in the context of free-oscillation atom interferometry and spatial multimode quantum memory.